Pathways to Inclusive Excellence for Black Students in STEM - Crittle, Chelsea. (Tufts University. Tisch Library., 2020)
Thesis (Ph.D.)--Tufts University, 2020.; Submitted to the Dept. of Psychology.; Advisor: Keith Maddox.; Committee: Christopher Marshburn, Samuel Sommers, and Jessica Remedios.; Keyword: Social psychology.; In recent years, colleges and universities have attempted to improve the collegiate experience for underrepresented students in Science, Technology, Engineering, and Mathematics (STEM) through inclusive excellence, a framework designed to help campuses integrate quality equity, diversity, and inclusion efforts into the core of institutional functioning (Williams, Berger, & McLendon, 2005). Across four studies, I examined the impact of identity-safety cues and bias confrontation on Black students' feelings of inclusion. In Study 1, I gathered evidence to gain an understanding of the types and frequencies of bias in STEM classrooms. In Study 2, I examined the question: Do identity-safety cues and direct bias confrontation increase feelings of inclusion for Black students? In Study 3, I examined the main question: Does emphasizing differences increase Black student's feelings of inclusion more than emphasizing equality? In Study 4, I examined the main question: Does direct confrontation increase Black students' feelings of inclusion more than educating the offender? I found evidence for Black STEM majors' experience of subtle and explicit racial bias in the forms of stereotyping and isolation in STEM classrooms (Study 1). When instances of racial bias occurred in the STEM classroom, professors who confronted bias were seen as more of an ally and bolstered inclusion, as measured by anticipated feelings of trust and comfort, towards the classroom setting for Black student onlookers (Studies 2-4). In addition, perceptions of professor support was found to be the mechanism driving the relationship between bias confrontation and feelings of trust and comfort (Studies 2-4). I did not find a significant impact of identity safety cue on feelings of inclusion or feelings towards the professor (Studies 2-4). Theoretical and practical considerations for the implementation of identity-safety cues and bias confrontation in the classroom context are discussed.